The Impact of the COVID-19 Pandemic on Fatal Road-Traffic Accidents: A Five-Year Study on Medicolegal Autopsies in Timis County, Romania - Ştefania Ungureanu; Veronica Ciocan; Camelia-Oana Mureșan; Emanuela Stan; Georgiana-Denisa Gavriliţă; Alexandra Sirmon; Cristian Pop; Alexandra Enache (Safety)
Road traffic accidents (RTAs) represent the key sign of the level of road safety. Romania once held the record for road deaths among European Union (EU) countries and as of 2023, it came second place. It is of utmost importance to assess whether measures that restricted human mobility during the coronavirus disease 2019 (COVID-19) pandemic led to a significant reduction in road fatalities. This study assesses the impact of the COVID-19 pandemic on victims of fatal RTAs by analyzing medicolegal autopsies from the Timisoara Institute of Legal Medicine (TILM), Timis County, Romania. Materials and methods: Medicolegal autopsy records of RTA victims from TILM in a 5-year period (2017–2021) were analyzed. Results: 395 cases (10.5%) were represented by victims of fatal RTAs. The reduction in the number of cases in the pandemic period was not statistically significant (p = 0.061) compared to the pre-pandemic period, but the number of victims of RTAs decreased by 17.6%. This highlights the importance of understanding the role of other risk factors in fatal RTAs, since a lesser volume of traffic did not cause a significant decrease in road fatalities. Male victims were predominant, with 18–50 years being the most affected age group. In the pandemic period, the most affected age groups were 31–40 (18.5%), followed closely by 41–50 (17.6%) and 18–30 (16.7%). In the pre-pandemic period, the first place was held by people in the age interval of 61–70 (20.5%), followed by 18–30 (19.2%). Drivers were the most involved type of road user, and a slight increase in the proportion of cyclists (13.9% from 10.5%) and motorcyclists (6.5% from 5.9%) was noted. Conclusions: Our findings show that measures implemented to control the COVID-19 pandemic may have had a positive effect on the reduction of RTAs, as shown by the information based on medicolegal autopsies in Timis County, Romania, but more attention needs to be focused on other risk factors. Further studies need to identify reasons for the small reduction in fatal injuries when the volume of traffic was reduced during mandated national lockdown.